CATEGORICAL APPARATUS OF THE OF CONTEXTUAL EDUCATION THEORY - A. A. VERBITSKIY (Высшее образование в России)
At the beginning of the article, the author approves the new rubric “Higher Education: A Critical Discourse”, which recently appeared in the journal. One of its goals is to discuss the scientific validity of the terms and concepts that have been widely used in modern pedagogical discourse. The author claims that such a discussion should take place only from the standpoint of a particular theory. The psychological and pedagogical theory of contextual education developed by the author’s scientific-pedagogical school can serve as a such theory. Further the article provides definitions of notions and terms revealing the essence of this theory.